Comments on "Monotone Functions in Sequential Circuits" - Ibaraki, T. (IEEE transactions on computers, 1974)
The above paper1 by Magó discusses the state assignment problem by means of monotone increasing (i.e., positive) next-state functions for both synchronous and asynchronous sequential networks. It may be interesting to note that the same subject for synchronous sequential networks has also been studied under a somewhat different title: "Fail-Safe Realization of Sequential Machines." This is because a realization with positive next-state functions (and positive output functions) results in a fail-safe sequential circuit in a certain sense.